Factors influencing identification of and response to intimate partner violence: a survey of physicians and nurses - Wathen C Nadine; Tutty Leslie; Beynon Charlene; Gutmanis Iris; MacMillan Harriet L (BMC Public Health, 2007)
Abstract Background Intimate partner violence against women (IPV) has been identified as a serious public health problem. Although the health care system is an important site for identification and intervention, there have been challenges in determining how health care professionals can best address this issue in practice. We surveyed nurses and physicians in 2004 regarding their attitudes and behaviours with respect to IPV, including whether they routinely inquire about IPV, as well as potentially relevant barriers, facilitators, experiential, and practice-related factors. Methods A modified Dillman Tailored Design approach was used to survey 1000 nurses and 1000 physicians by mail in Ontario, Canada. Respondents were randomly selected from professional directories and represented practice areas pre-identified from the literature as those most likely to care for women at the point of initial IPV disclosure: family practice, obstetrics and gynecology, emergency care, maternal/newborn care, and public health. The survey instrument had a case-based scenario followed by 43 questions asking about behaviours and resources specific to woman abuse. Results In total, 931 questionnaires were returned; 597 by nurses (59.7% response rate) and 328 by physicians (32.8% response rate). Overall, 32% of nurses and 42% of physicians reported routinely initiating the topic of IPV in practice. Principal components analysis identified eight constructs related to whether routine inquiry was conducted: preparedness, self-confidence, professional supports, abuse inquiry, practitioner consequences of asking, comfort following disclosure, practitioner lack of control, and practice pressures. Each construct was analyzed according to a number of related issues, including clinician training and experience with woman abuse, area of practice, and type of health care provider. Preparedness emerged as a key construct related to whether respondents routinely initiated the topic of IPV. Conclusion The present study provides new insight into the factors that facilitate and impede clinicians' decisions to address the issue of IPV with their female patients. Inadequate preparation, both educational and experiential, emerged as a key barrier to routine inquiry, as did the importance of the "real world" pressures associated with the daily context of primary care practice.